Vulnerable newborn types: analysis of subnational, population‐based birth cohorts for 541 285 live births in 23 countries, 2000–2021 - Daniel J. Erchick; Elizabeth Hazel; Joanne Katz; A. C. C. Lee; Maureen H. Diaz; Lee Wu; Sachiyo Yoshida; Rajiv Bahl; Carlos Grandi; Alain Labrique; M. Rashid; Salahuddin Ahmed; et al. (2023)
Abstract Objective To examine prevalence of novel newborn types among 541 285 live births in 23 countries from 2000 to 2021. Design Descriptive multi‐country secondary data analysis. Setting Subnational, population‐based birth cohort studies ( n = 45) in 23 low‐ and middle‐income countries (LMICs) spanning 2000–2021. Population Liveborn infants. Methods Subnational, population‐based studies with high‐quality birth outcome data from LMICs were invited to join the Vulnerable Newborn Measurement Collaboration. We defined distinct newborn types using gestational age (preterm [PT], term [T]), birthweight for gestational age using INTERGROWTH‐21st standards (small for gestational age [SGA], appropriate for gestational age [AGA] or large for gestational age [LGA]), and birthweight (low birthweight, LBW [<2500 g], nonLBW) as ten types (using all three outcomes), six types (by excluding the birthweight categorisation), and four types (by collapsing the AGA and LGA categories). We defined small types as those with at least one classification of LBW, PT or SGA. We presented study characteristics, participant characteristics, data missingness, and prevalence of newborn types by region and study. Results Among 541 285 live births, 476 939 (88.1%) had non‐missing and plausible values for gestational age, birthweight and sex required to construct the newborn types. The median prevalences of ten types across studies were T+AGA+nonLBW (58.0%), T+LGA+nonLBW (3.3%), T+AGA+LBW (0.5%), T+SGA+nonLBW (14.2%), T+SGA+LBW (7.1%), PT+LGA+nonLBW (1.6%), PT+LGA+LBW (0.2%), PT+AGA+nonLBW (3.7%), PT+AGA+LBW (3.6%) and PT+SGA+LBW (1.0%). The median prevalence of small types (six types, 37.6%) varied across studies and within regions and was higher in Southern Asia (52.4%) than in Sub‐Saharan Africa (34.9%). Conclusions Further investigation is needed to describe the mortality risks associated with newborn types and understand the implications of this framework for local targeting of interventions to prevent adverse pregnancy outcomes in LMICs.